Educação especial e o direito à educação: um estudo sobre alfabetização em sala de recursos multifuncionais na escola do campo - Eloy, Adriana Cristina Morais (Universidade Federal de São Carlos, 2020)
Considering that literacy, in a literate society is a needed condition to access scientific, artistic and philosophical knowledge, historically systemized transformed at school, in school knowledge, this thesis has as an objective analyzing the literacy process of the students who attend the multifunctional resource room, specifically; a) understand historically the p olitics to special and inclusive education and its implementation after 1980s;b) characterize the conditions in which the educational process is being held in the rural school and the multifunctional resources room in Porto Feliz; c) identify the research subject d) deepen the theoretical knowledge about the different concepts of literacy performed by the teachers. As a quantitative and qualitative research, and bibliographic, documental and field type, it was used as the procedure of research semi- structured interviews, questionnaire, observation of administrative papers and didactic -pedagogical papers. Through bibliographic research, it was possible to assess which authors had researched about special education in relation to our objective. For the empiric study, it was chosen a rural school in the city of Porto Feliz, SP. The subjects were five students who attend the multifunctional resource room (first to fifth grade), five family members, the specialist teacher, four teachers for the regular classes, the coordinator, the vice- principal, the representing of Education Division, also responsible for the special education in the city. The data collection happened in 2019, between the months of July and December. The analysis was grounded on theoretical an d methodological of historycritical pedagogy, which is supported, by the historical materialism and dialectic. The preliminary results show that the literacy in resource rooms is partially different from the procedures used in regular rooms, specifically as the didactic resources used, because of the educational relation, an individual attendance brings. The differences observed indicate a progress in the literacy process of those children attended by the resource room, but in a limited way. On the other hand, special education carries the mark of welfare, relying on the teacher to bring solutions and answers that should be given by the medical field, the lack of theoretical instruments to understand learning, specifically the literacy process, and evaluation, the resource room became the only place where there is specific treatment to students` needs. The pedagogical conception remains the same as the regular room, seeing learning or not as a natural and biological way. Finally, the historical-critical pedagogy is one of the pedagogical theory necessary to ground the teacher to assist students, being students from special education or not.
Special Education and the right to education: one study about literacy on multifunctional resource room in a rural school
Keywords: Pedagogia Histórico-Crítica; Educação Especial; Direito à Educação; Escola do Campo; Alfabetização; Historical-Critical Pedagogy; Special Education; Education Rights; Rural Schools; Literacy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO